2015
DOI: 10.1089/dna.2015.2810
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the TCRζ Expression, Polyclonal Expansion, and Activation of T Cells from Patients with Acute Myeloid Leukemia After IL-2, IL-7, and IL-12 Induction

Abstract: Defective T cell receptor (TCR) signaling resulting in lower T cell function plays a crucial role in the pathogenesis of T cell immunodeficiency in leukemia. Previous studies have indicated that lower TCRf levels are a common characteristic of patients with leukemia, and upregulating TCRz could partially recover T cell function. In this study, we characterized the effect of the stimulating factor induction on the TCRf, Zap-70, and FceRIc levels, IFN-g secretion, and the distribution and clonal expansion of TCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Obvious, most Vδ subfamily T cells could be detected in most samples at the time point from 117 to 190 weeks, however, polyclonal expansion or oligoclonally expanded T cells with different CDR3 lengths indicated that came from different clones and would be the unspecific expansion. This T cell expansion may be enhanced by IL-2 and IFN-γ which were used with DLI [16, 17]. However, even the relapse with the same Vδ5 leukemic clone, whether there was evolution in another molecule that may affect the biological behavior of a leukemic clone remains unclear, this may be identified by deep sequencing of the patient samples, which were collected at each instance of disease recurrence [1820].…”
Section: Discussionmentioning
confidence: 99%
“…Obvious, most Vδ subfamily T cells could be detected in most samples at the time point from 117 to 190 weeks, however, polyclonal expansion or oligoclonally expanded T cells with different CDR3 lengths indicated that came from different clones and would be the unspecific expansion. This T cell expansion may be enhanced by IL-2 and IFN-γ which were used with DLI [16, 17]. However, even the relapse with the same Vδ5 leukemic clone, whether there was evolution in another molecule that may affect the biological behavior of a leukemic clone remains unclear, this may be identified by deep sequencing of the patient samples, which were collected at each instance of disease recurrence [1820].…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation and cDNA synthesis were performed according to the manufacturer's protocol. 30,31 The expression level of PD-1, PD-L1, CTLA-4, and the β2-microglobulin (β2-MG) reference gene was determined by SYBR Green I real-time PCR as previously described. 32 The primers (Table 2) were purchased from Shanghai Sangon Biological Engineering Technology & Services Co. in China.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…PCR was performed as described in previous studies. 30,33 Briefly, 25-μl PCRs were performed with approximately 1 μl cDNA, 0.5 μM of each primer (PD-1-for and PD-1rev for the PD-1 gene, PD-L1-for and PD-L1-rev for the PD-L1 gene, CTLA-4-for and CTLA-4-rev for the CTLA-4 gene, and β2M-for and β2M-rev for the β2-MG gene), 2.5× RealMasterMix (11.25 μl) (Tiangen, Beijing). After an initial denaturation at 95°C for 2 hours, 45 cycles consisting of 95°C for 15 minutes and 60°C for 1 hour were performed using an MJ Research DNA Engine Opticon 2 PCR cycler (BIO-RAD, USA).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…These so‐called tumor‐specific cytotoxic T cells may display cytotoxic activity against AML cells . However, it is also known that T cells in AML patients display lower activation and antileukemia effects . To further address this phenomenon, the expression and function of the TCR signaling pathway, activation and inhibitory receptors in T cells were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, it is also known that T cells in AML patients display lower activation and antileukemia effects. 35,36 To further address this phenomenon, the expression and function of the TCR signaling pathway, activation and inhibitory receptors in T cells were analyzed. For example, lower TCR expression reduced T cell activation and cytotoxicity, 8,35 and up-regulation of PD-1 and Tim-3 significantly reduced T cell function and promoted T cell exhaustion.…”
Section: Discussionmentioning
confidence: 99%